Radiation-hard plastic scintillators with 3-hydroxyflavone derivatives - Gurkalenko, Yu.A.; Zhmurin, P.N.; Lebedev, V.N.; Pereymak, V.N.; Svidlo, O.V. (Functional Materials, 2016)
New compositions of radiation-hard plastic scintillators (PS) with content of 3-hydroxyflavone (3HF) derivatives are proposed. It is shown, that the new PS based on polystyrene with these dopants have both the higher radiation hardness and the higher light output, than PS with original 3HF.